2022
DOI: 10.1002/cssc.202102528
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxy‐Group‐Functionalized Single Crystal of Copper(II)‐Porphyrin Complex for Electroreduction CO2 to CH4

Abstract: Purposefully developing crystalline materials at molecular level to improve the selectivity of electroreduction CO2 to CH4 is still rarely studied. Herein, a single crystal of copper(II) complex with hydroxy groups was designed and synthesized, namely 5,10,15,20‐tetrakis(3,4‐dihydroxyphenyl)porphyrin copper(II) (Cu‐PorOH), which could serve as a highly efficient heterogeneous electrocatalyst for electroreduction of CO2 toward CH4. In 0.5 m KHCO3, Cu‐PorOH gave a high faradaic efficiency of 51.3 % for CH4 and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…3 In this case, it has been reported that hydroxyl groups can stabilize the intermediates by forming hydrogen bonds, thus lowering the energy barrier and promoting the formation of CHO*. 19 To confirm this speculation, we further conducted density functional theory (DFT) calculations on these key reaction pathways for the conversion of CO* on the Ni(OH) 2 surface with and without PHF (Figure S14). 3,46 As depicted in Figure 4d, the DFT calculation displays that on the Ni(OH) 2 surface, the transition from CO* (+0.95 eV) to CHO* (+2.14 eV) involves an energy-consuming process (+1.2 eV) with a considerable barrier that must be overcome.…”
Section: Photocatalytic Reaction Mechanismmentioning
confidence: 75%
See 1 more Smart Citation
“…3 In this case, it has been reported that hydroxyl groups can stabilize the intermediates by forming hydrogen bonds, thus lowering the energy barrier and promoting the formation of CHO*. 19 To confirm this speculation, we further conducted density functional theory (DFT) calculations on these key reaction pathways for the conversion of CO* on the Ni(OH) 2 surface with and without PHF (Figure S14). 3,46 As depicted in Figure 4d, the DFT calculation displays that on the Ni(OH) 2 surface, the transition from CO* (+0.95 eV) to CHO* (+2.14 eV) involves an energy-consuming process (+1.2 eV) with a considerable barrier that must be overcome.…”
Section: Photocatalytic Reaction Mechanismmentioning
confidence: 75%
“…15−17 In this context, the strategic utilization of surface hydroxyl groups to establish synergistic catalytic interactions with active sites enables the conversion of CO 2 into deep hydrogenation product CH 4 . 18,19 However, constructing synergistic active sites by hydroxyl groups necessitates their suitable positioning to ensure the formation of an effective active region. 17,20 Moreover, the stable presence of hydroxyl groups is indispensable, posing a challenge for surface lattice hydroxyls in achieving both aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as depicted in Figure S10, the Cu 2 O-HA catalyst undergoes the same reduction process to metallic Cu after electrochemical reaction as observed for the Cu 2 O-800 catalyst. ATR-FTIRS showed that the free CO stretching vibration of HA (at 1704 cm –1 ) was split into asymmetric and symmetric COO – stretching vibrations at 1520 and 1420 cm –1 upon bounding to Cu surface, implying the successful capping of HA on the Cu 2 O catalyst (Figure S11). As demonstrated in Figure S12a, the FE of the C2+ products exhibited a significant decrease in comparison to that observed for the Cu 2 O-800 catalyst, indicating a notable discrepancy.…”
Section: Resultsmentioning
confidence: 99%
“…For the OD-Cu-1200 catalysts, they show a similar C2+ product FE but a higher CO FE at a higher applied potential on comparison with OD-Cu-0 catalysts (Figure S22). Because the hydroxyl species on the catalyst surface influences the binding of intermediates *CO, we posited that higher hydroxyl coverage would stabilize more intermediate *CO on the surface with the applied potential increase. , So, the higher hydroxyl coverage near the OD-Cu-1200 catalyst surface causes the stabilized *CO overload and thus an increase of free energy change for *CO dimerization. In the case of Cu 2 O-300 catalysts with low coverages of surface hydroxyl, the HER is preferred more (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the use of the direct air capture (DAC) technology is considered vital for successfully controlling CO 2 removal from mobile emission sources . In recent years, DAC has attracted increasing attention as a supplementary alternative to CCUS, with the ability to absorb CO 2 straight from the atmosphere, independent of the source location . As a result, the DAC technology plays a crucial role in mitigating emissions from difficult-to-decarbonize sectors such as aviation, shipping, and remote industries .…”
Section: Introductionmentioning
confidence: 99%